The Effect Of Contextual Teaching And Learning Model On Students' Mathematical Critical Thinking Skills - Sitanggang, Fortina Julianta; Tambunan, Lois Oinike; Sinaga, Christa Voni Roulina (CV Putra Publisher, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning learning model on students' mathematical critical thinking skills at Cinta Rakyat 3 Private Junior High School, Pematangsiantar. This study uses a quantitative approach. The method used by the researcher is an experimental method. This research method was chosen to see how much influence the Contextual Teaching and Learning learning mode has on students' mathematical critical thinking skills on the material of curved cylinder side solids at Cinta Rakyat 3 Private Junior High School, Pematangsiantar. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the use of the Contextual Teaching and Learning learning mode on students' mathematical critical thinking skills on the material of curved cylinder side solids, grade IX of Cinta Rakyat 3 Private Junior High School, Pematangsiantar. This influence is shown through the regression equation Y = 22.457 + 0.743X with b = 0.743. By using the t-test, namely t_calculated > t_table = (10,364 > 3,583) it shows that the significance and by using the coefficient of determination it can be seen that the influence is 79.3%.